Strawberry Shortcake. The Berryfest Princess movie - Cummer, Anna, 1977-; Bail, Ashleigh; Nilson, Ingrid; Twentieth Century Fox Home Entertainment, Inc. (Culver City, Calif. : 20th Century Fox Home Entertainment, 2010)
Celebrate Strawberry Shortcake's new royal movie adventure, in which Strawberry has just been appointed Berryfest Princess of the festival.
Title from container.
Special features: A Berry Royal sing-a-long; printable coloring pages; trailer.
Camera, Jamie Cammon ; art directors, Ganhua Hu, Xiaomin Ye ; editor, Steve "Sketch" Vallino ; score by Marco Luciani, Chip Whitewood.
Voices: Anna Cummer, Ashleigh Ball, Ingrid Nilson, Janyse Jaud, Britt McKillip, Andrea Libman, Paul Dobson, Scott McNeil.
Not rated.
DVD, widescreen (1.78:1) presentation; Dolby Digital surround.
Keywords: Strawberry Shortcake (Fictitious character) -- Juvenile films; Princesses -- Juvenile films; Coronations -- Juvenile films; Friendship -- Juvenile films; Fantasy films; Action and adventure films; Children's films; Animated films; Feature films; Fiction films